Uncovering the barriers to exclusive breastfeeding for mothers living in Dhaka's slums: a mixed method study - Halima Khatun; Carly A Comins; Rajesh Shah; M Munirul Islam; Nuzhat Choudhury; Tahmeed Ahmed (BMC, 2018)
Abstract Background Despite the substantial impact on child and maternal health, breastfeeding practices for infants remain at the suboptimum level in Bangladesh. Yet the understanding of why these practices are suboptimal, especially surrounding urban slum dwelling mothers, is unclear. The purpose of this study was to assess early infant feeding practices, examine associations with maternal factors, and uncover the facilitators and barriers to early feeding practices in selected slums of Dhaka, Bangladesh. Methods A mixed method study was conducted from June to September 2016 using both quantitative and qualitative methods among mothers with children under the age of 6 months. The survey included 342 mother-infant pairs and 18 in-depth interviews were conducted. Univariate and multiple logistic regression was used to determine status of early infant feeding practices and factors associated with exclusive breastfeeding (EBF) within the previous 24 h. Transcripts were coded to uncover the facilitators and barriers surrounding early infant feeding practices. Results Sixty four percent (220/342) of mothers initiated breastfeeding within 1 h, 96.5% (330/342) reported feeding colostrum, and 36.3% (124/342) infants were EBF in the last 24 h. After adjusting for child gender, maternal age, education, diet and household income; infant's age (adjusted odds ratio (AOR) for 61-120 days 6.42; 95% CI 3.42, 12.1; AOR for 121-180 days 45.6; 95% CI 18.33, 113.45), prelacteal feeding (AOR 2.53; 95% CI 1.14, 4.58), lack of planning for EBF during pregnancy (AOR 4.06; 95% CI 1.09, 15.12) and infants delivered by cesarean section (AOR 2.76; 95% CI 1.34, 5.67) were negatively associated with EBF. During the 18 interviews, eight mothers reported a cesarean delivery and none of these mothers initiated breastfeeding within 1 h or exclusively breastfed. Moreover, all eight mothers gave their infants prelacteal feeds. Conclusions The status of early infant feeding practices in Dhaka's slums was poor. The negative impact of cesarean section on all early infant feeding practices was evident in both quantitative and qualitative analysis.